The role of microtransactions in Internet Gaming Disorder and Gambling Disorder: A preregistered systematic review. (June 2022) - Raneri, Phillip C.; Montag, Christian; Rozgonjuk, Dmitri; Satel, Jason; Pontes, Halley M.
Highlights: Microtransaction engagement is associated with gaming and gambling disorder. Loot boxes appear to pose greater risk for addiction than other microtransactions. Greater in-game expenditure increased with risk of gambling disorder. Prevalence rates of gaming and gambling disorder varied significantly. Abstract: Recently there has been increased interest in understanding the relationship between microtransactions, gaming, and gambling. This review aimed to synthesise the evidence on the relationship between microtransactions, 'Internet Gaming Disorder' (IGD), and Gambling Disorder in order to report on the: psychometric assessments used, sampling and demographic information, study design and sampling methods, relationships between microtransactions and both IGD and gambling disorder. Inclusion criteria included: refereed studies quantifying microtransactions and/or loot boxes examining their relationship with IGD and/or gambling disorder that were published between 2013 and 2021. Electronic databases were searched and the results were synthesised qualitatively. 14 studies were included. The quality of the evidence was 'Good' and clear positive relationships between microtransactions and both IGD and gambling disorder were identified. These relationships apply more to loot boxes than other microtransactions, and risky loot box use was identified as a possible mediator of these relationships. Additionally, microtransaction expenditure increased with the risk of gambling disorder. There is some evidence that adolescents who purchase loot boxes may be more at risk of developing gambling disorder. External validity is limited due to the cross-sectional nature of the evidence, the use of convenience sampling, and the predominantly Western samples resulting in non-representative samples. Prevalence rates of IGD and gambling disorder varied significantly across studies and were different to general prevalence rates. We conclude that there is a need to develop consistent methods for assessing IGD and microtransaction engagement in future research. Implications for policy-makers and future research are discussed.